Pyrocardan Scaphotrapeziotrapezoid Joint Arthroplasty for Isolated Osteoarthritis: Results after a Mean Follow-Up of 5 Years - Cholley-Roulleau, Martin; Bouju, Yves; Lecoq, Flore-Anne; Fournier, Alexandre; Bellemère, Philippe (Journal of Wrist Surgery, 2021)
Background Isolated scaphotrapeziotrapezoid (STT) osteoarthritis (OA) mainly develops in women over 50 years of age in a bilateral manner. Many surgical treatments are available, including distal scaphoid resection with or without interposition, trapeziectomy, and STT arthrodesis. However, there is a controversy about which procedure is the most effective.Purposes The purpose of this study was to report the outcomes of the Pyrocardan implant for treating STT isolated OA at a mean follow-up of 5 years.Patients and Methods Consecutive patients who underwent STT arthroplasty using the Pyrocardan were reviewed retrospectively by an independent examiner who performed a clinical and radiological evaluation.Results The mean follow-up time was 5 years (range 3–8 years). Thirteen patients (76%) were followed for more than 5 years. Between the preoperative assessment and the last follow-up, pain levels decreased significantly. There was no significant difference in the mean Kapandji opposition score. Grip and pinch strengths were 88 and 91% of the contralateral side. The active range of motion in flexion–extension and radioulnar deviation was not significantly different to the contralateral side (119° vs. 121° and 58° vs. 52°, p > 0.1). Functional scores were improved significantly. No identifiable differences were found in the radioscaphoid, capitolunate, and scapholunate angles before and after surgery. In three cases, the preoperative dorsal intercalated scapholunate instability (DISI) failed to be corrected. In one case, DISI appeared after the procedure. There was one asymptomatic dislocation of the implant. Calcification around the trapezium and/or distal scaphoid was found in four cases. The survival rate of the implant without reoperation was 95%.Conclusions In the medium term, Pyrocardan implant is an effective treatment for STT OA as it reduces pain, increases grip strength, and maintains wrist mobility. This is consistent with the results of other published case series using pyrocarbon implants. It provides a high rate of patient satisfaction. Nevertheless, the surgical procedure must be done carefully to avoid STT ligament damage, periarticular calcifications, or dislocation.
Keywords: pyrocarbon; osteoarthritis; scaphotrapeziotrapezoid; wrist